Evaluasi Proses Pendidikan Karakter Disiplin Peserta Didik di SMP Negeri 7 Palembang - Pebriyanti, Dina; Niswah, Choirun; Ibrahim, Ibrahim; Febriyanti, Febriyanti (Indo-MathEdu Intellectuals Journal, 2024)
The aim of this study is to understand how the evaluation process of student disciplinary character education is conducted at SMP Negeri 7 Palembang. This study uses a descriptive method with a qualitative approach. The study involved 8 informants, including the Principal, Vice Principal, teaching staff, non-teaching staff, students, and 3 parents. Data collection techniques employed include data reduction, data presentation, data verification, and conclusion drawing. The validity of the data was ensured through triangulation, consisting of source triangulation, time triangulation, and technique triangulation. The results of the analysis show that the evaluation has gone well as expected. This is achieved through coordination involving all stakeholders, with plans and objectives set by the principal to all parties. Each stakeholder is required to work together and discuss in advance to ensure that coordination runs smoothly, both in learning and habituation. This coordination is carried out regularly every month. Furthermore, intracurricular implementation involves the application of disciplinary character values in all subjects, attendance recording, and habituation that associates disciplinary character in students. Supervision is carried out by monitoring teacher performance through daily observation and attendance, as well as by building a school culture that supports an environment that pays attention to the character of discipline.